Fracture development and controlling factors at metamorphic buried-hill reservoirs of Bozhong 19-6 gas field in Bohai Bay, East China - Mi, Lijun; Fan, Tingen; Fan, Hongjun; Niu, Tao; Gong, Lei; Su, Xiaocen; Sun, Yonghe; Cheng, Yuqi (Frontiers in Earth Science, 2023)
Fractures of multi-scales and multi-origins are primary storage space and effective seepage channels for metamorphic buried-hill reservoirs. They not only communicate various pores to enhance storage and permeability capacity, but also are essential for high yields. Fracture development and its controllers at metamorphic buried-hill reservoirs of Bozhong 19-6 Gas Field were investigated based on imaging log, core data, experiments, e.g., thin sections and scanning electron microscope images, and fracture description on outcrops. Results show that structural fractures, weathering fractures and dissolution fractures were developed in the metamorphic buried-hill reservoirs in the study area, among which structural fractures and weathering fractures were the most popular ones. However, fracture types varied obviously among different structure positions. Lithology, fault, weathering crust and ancient landform were primary factors affecting fracture distribution. Fractures were prone to be developed at lithology with high bright mineral contents. Faults were characterized by a dual structure including core and fractured zone. Fracture density followed a decreasing trend with increasing distance from faults. Fractured zone could be identified when fracture density was consistent with regional fracture density. The width of the fractured zone was determined by factors such as fault scale and structure location. Well-connected weathering fractures were popular at the leached unit, with structural fractures of secondary importance. The unweathered unit was dominated by structural fractures with low density.